2022
DOI: 10.1186/s12874-022-01586-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of evidence on the use of ecological momentary assessments to monitor health outcomes after traumatic injury: rapid systematic review

Abstract: Background With the increasing use of mobile technology, ecological momentary assessments (EMAs) may enable routine monitoring of patient health outcomes and patient experiences of care by health agencies. This rapid review aims to synthesise the evidence on the use of EMAs to monitor health outcomes after traumatic unintentional injury. Method A rapid systematic review of nine databases (MEDLINE, Web of Science, Embase, CINAHL, Academic Search Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Evidence also indicates that EMAs provide ecological validity of whether associations are significant in relation to typical settings of everyday life [ 67 , 68 ]. PA measurement using EMAs provide context, improves data validity through reduction of recall bias and data entry errors as participants are not required to retrospectively recall their behaviours [ 69 , 70 ]. EMAs reduce participant burden by using digital reminders/ nudges that can be triggered on participants’ phones based on predefined time and location [ 69 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence also indicates that EMAs provide ecological validity of whether associations are significant in relation to typical settings of everyday life [ 67 , 68 ]. PA measurement using EMAs provide context, improves data validity through reduction of recall bias and data entry errors as participants are not required to retrospectively recall their behaviours [ 69 , 70 ]. EMAs reduce participant burden by using digital reminders/ nudges that can be triggered on participants’ phones based on predefined time and location [ 69 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…PA measurement using EMAs provide context, improves data validity through reduction of recall bias and data entry errors as participants are not required to retrospectively recall their behaviours [ 69 , 70 ]. EMAs reduce participant burden by using digital reminders/ nudges that can be triggered on participants’ phones based on predefined time and location [ 69 , 71 ]. In addition, EMAs can also be self-triggered by participants, which allows them some level of personalization to their needs [ 69 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, participants took less time to respond to survey notifications received by text message than email. Most existing EMA studies have not reported completion rates by notification method (email vs. text message), have not provided participants with different notification options [16], [44], [45], or have used mobile applications with built-in prompts for participants to take assessments at appropriate intervals [46], [47]. However, our results are consistent with one previous study on drug use among adults in non-urban areas, in which EMA completion rates were higher when notifications were sent via text message compared to email [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, EMA is not without its limitations. Mitchell et al's rapid review of EMA in monitoring outcomes following traumatic injury highlights how the type of technology used to deliver EMAs affects the quality of data, that EMA completion rates tend to reduce over time, and that intensive self-monitoring may affect participants behaviour and responses, a phenomenon known as reactivity (Mitchell et al, 2022). Optimising the usability of EMAs is therefore essential in optimising data quality and exploring users experiences of EMA may help to understand the potential effects of intensive self-monitoring.…”
Section: Introductionmentioning
confidence: 99%